المسؤولية المدنية و الجزائية لمحافظي الحسابات في شركة المساهمة - نورالدين, صحراوي (Université de M'sila, 2019)
أمام السلطات القانونية الواسعة التي يتمتع بها محافظ الحسابات في مراقبة الشركة كان من المنطق ترتيب مسؤوليات حتى لا يتجاوز حدود مهامه و لا يستعملها فيما يضر المشروع و المستثمرين. فان تجاوزه لحدود الاتفاق أو ما التزم به قانونا يؤدي إلى مسائلته مدنيا و ترتيب عقوبة مدنية تهدف إلى إصلاح الضرر الذي سببه. أما إذا كان تجاوزه لقاعدة قانونية آمرة أو ناهية يرتب عليها القانون عقوبة جزائية يؤدي إلى قيام مسؤوليته الجزائية. Given the vast legal powers of the auditor in the control of the company, it made sense to arrange responsibilities so as not to exceed the limits of its functions and not to use them to the detriment of the project and investors. Its violation of the terms of the agreement or its commitment to a law leads to its civil liability and the order of a civil sanction intended to repair the damages caused. However, if it exceeds a rule of imperative or criminal law under which the law establishes a criminal sentence that entails criminal liability.
Keywords: المسؤولية المدنية. المسؤولية الجزائية. محافظ الحسابات. شركة المساهمة